2005
DOI: 10.1246/cl.2005.1586
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for the Preparation of Carboxamides by Dehydration Condensation Using Tetrakis(1,1,1,3,3,3-hexafluoro-2-propoxy)silane

Abstract: The use of tetraalkoxysilanes, particularly tetrakis(perfluoroalkoxy)silanes, in dehydration condensation of carboxylic acids with amines was investigated. Tetrakis(1,1,1,3,3,3-hexafluoro-2-propoxy)silane, Si[OCH(CF3)2]4, prepared easily from silicon tetrachloride and sodium 1,1,1,3,3,3-hexafluoro-2-propoxide, was found to be an effective dehydrating reagent for preparing various carboxamides in good to high yields from the corresponding carboxylic acids and amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Mukaiyama and co-workers recently have designed original dehydrating agents, 8 tetrakis(alkoxy)silane Si(OR) 4 , and applied them to condensation reactions. 9, 10 We also have reported the direct amidation of fatty acids and long-chain amines catalyzed by multivalent metal salts such as FeCl 3 •6H 2 O catalyst. 11 Although these methods circumvent the utilization of corrosive and excess of reagents, considering the enhanced demands for environmentally benign chemistry, there still remains a task of improving the reusability of the catalyst and the facilitation of work-up.…”
mentioning
confidence: 96%
“…Mukaiyama and co-workers recently have designed original dehydrating agents, 8 tetrakis(alkoxy)silane Si(OR) 4 , and applied them to condensation reactions. 9, 10 We also have reported the direct amidation of fatty acids and long-chain amines catalyzed by multivalent metal salts such as FeCl 3 •6H 2 O catalyst. 11 Although these methods circumvent the utilization of corrosive and excess of reagents, considering the enhanced demands for environmentally benign chemistry, there still remains a task of improving the reusability of the catalyst and the facilitation of work-up.…”
mentioning
confidence: 96%
“…In a third communication in 2005, 42 Mukaiyama et al screened (Scheme 12) various alkoxy silanes for their amide Scheme 6 (A) Example of scope of peptides formed with HSi(OCH(CF 3 ) 2 ) 3 (SR17). 35 See Table 1, entry 19 for full substrate scope.…”
Section: Tetrakis(111333-hexafluoro-2-propoxy)silanementioning
confidence: 99%
“…Mukaiyama found that simple alkoxy silanes such as tetramethyl orthosilicate (TMOS -CAUTION: fatal if inhaled, GHS: H330 -SR23) and tetraethyl orthosilicate (TEOS -SR24) gave only low conversion when used as stoichiometric coupling reagents for amidation at room temperature in THF. 42 Sheppard also found that SR23 gave low conversion when used as a stoichiometric coupling reagent in refluxing acetonitrile. 43 However, Braddock et al successfully developed a TMOS based protocol in refluxing toluene to afford high yields of pure amide products from aliphatic and aromatic carboxylic acids with primary, cyclic & acyclic secondary amines and anilines as well as other challenging amidations (Scheme 13).…”
Section: Tetramethyl Orthosilicatementioning
confidence: 99%
“…This protocol also successfully transfers to the inherently more difficult amidations of benzoic acid as a representative aromatic carboxylic acid with primary amines and cyclic secondary amines giving amides 8 – 10 (Figure , bottom) making this method highly competitive with other methods reported for these direct amidation classes. To effect the still more challenging amidations of benzoic acid with acyclic secondary amines and anilines to give amides 11 and 12 , higher reaction concentrations, an excess of carboxylic acid (for 12 ), and the use of 4 Å MS sieves suspended in the reaction headspace were necessary. There is only limited literature precedent for high yielding reactions of the former ,, and latter amidation reaction types, and to the best of our knowledge, no quantitative yields have been reported. The quantitative yield obtained for amide 12 is therefore notable .…”
mentioning
confidence: 99%
“…8 However, limitations remain, including multistep synthesis of catalysts, the use of nonstoichiometric acid-to-amine quantities, extended reflux with azeotropic removal of water in refluxing aromatic solvents, the need for chromatographic purification of the amide product, and/or the inability to mediate the more challenging amidation types. 9 In the mid-2000s, a series of seminal papers by Mukaiyama describe the use of imidazoylsilanes, 10 tetrakis(pyridine-2yloxy)silane, 11 and tetrakis(1,1,1,3,3,3-hexafluoro-2-propoxy)silane 12 as reagents for direct amidation reactions at room temperature in ethereal solvents. These silicon-based reagents perform excellently for all the major classes of acid−amine combinations, but require prior synthesis from tetrachlorosilane, and with the exception of the latter silane, they do not afford pure amide upon workup: further purification is required to remove the ancillary ligand.…”
mentioning
confidence: 99%